2016
DOI: 10.1021/acs.langmuir.6b02509
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Crystalline Star-Shaped Supergelator Exhibiting Aggregation-Induced Blue Light Emission

Abstract: A family of closely related star-shaped stilbene-based molecules containing an amide linkage are synthesized, and their self-assembly in liquid-crystalline and gel states was investigated. The number and position of the peripheral alkyl tails were systematically varied to understand the structure-property relation. Interestingly, one of the molecules with seven peripheral chains was bimesomorphic, exhibiting columnar hexagonal and columnar rectangular phases, whereas the rest of them stabilized the room-temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 46 publications
3
20
0
Order By: Relevance
“…Therefore, the presence of an ordered rectangular columnar (Col ro ) mesophase at ambient temperature, but a disordered rectangular columnar (Col rd ) mesophase at higher temperatures seems to be reasonable. The observed phase sequence of one (or two) rectangular columnar phases at lower temperatures followed by a hexagonal columnar phase at higher temperatures is in good agreement with similar phase behavior of non-discoid [66][67][68][69][70] and discoid mesogens 71,72 and has been examined theoretically. [73][74][75] However, the lattice parameters changed slightly during the Col ro -Col rd transition (a = 0.7 Å, b = 0.2 Å), although a small but distinct endothermal peak was visible in the DSC curve (Figure 5c, H = 1.3 kJ mol -1 ).…”
Section: Studies On Mesomorphism Mesomorphic Properties Of Diazafluosupporting
confidence: 77%
“…Therefore, the presence of an ordered rectangular columnar (Col ro ) mesophase at ambient temperature, but a disordered rectangular columnar (Col rd ) mesophase at higher temperatures seems to be reasonable. The observed phase sequence of one (or two) rectangular columnar phases at lower temperatures followed by a hexagonal columnar phase at higher temperatures is in good agreement with similar phase behavior of non-discoid [66][67][68][69][70] and discoid mesogens 71,72 and has been examined theoretically. [73][74][75] However, the lattice parameters changed slightly during the Col ro -Col rd transition (a = 0.7 Å, b = 0.2 Å), although a small but distinct endothermal peak was visible in the DSC curve (Figure 5c, H = 1.3 kJ mol -1 ).…”
Section: Studies On Mesomorphism Mesomorphic Properties Of Diazafluosupporting
confidence: 77%
“…C 3 OPV2 , a molecule with alkoxy chains at 3,4-positions is able to gelate organic solvents, whereas C 3 OPV3 , a molecule with alkoxy chains at 3,5-positions, neither forms gel nor shows any LC properties. This study illustrates the important role of alkoxy chains in the design of functional molecules with distinctly different properties 48,6668 and hence can be applied to several of the existing systems for their rational conversion to functional soft materials.…”
Section: Discussionmentioning
confidence: 86%
“…In 2016, Pathak et al synthesized a series of star-shaped liquid crystalline gelators based on the stilbene-structure showing AIE activity (STI-1-5) in the gel state as well as in the mesophase and the solid state (Figure 28A). [68] A crucial structural element of the mesogens is the amide linkages, which induces columnar stacking of the mesogens by intermolecular hydrogen bonding. A comprehensive structure-property relationship study revealed that the nature and thermal stability of the mesophase strongly depend on the number and length of the peripheral alkyl chains.…”
Section: Hydrogen-bonded Assembliesmentioning
confidence: 99%